2007
DOI: 10.1093/ajcn/85.4.1098
|View full text |Cite
|
Sign up to set email alerts
|

A functional 19-base pair deletion polymorphism of dihydrofolate reductase (DHFR) and risk of breast cancer in multivitamin users

Abstract: The DHFR 19-bp deletion polymorphism affects the transcription of DHFR gene in humans. Multivitamin supplements may place a subgroup of women (ie, those with the -19-bp allele) at elevated risk of developing breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 16 publications
2
64
1
2
Order By: Relevance
“…Several variations of DHFR have been found in noncoding regions, which may relate to the variability of DHFR activity found in the current study. A 19 bp deletion polymorphism within intron 1 (43) has been found to enhance gene expression (44,45). This increased expression was thought to be due to loss of another Sp1 transcription factor binding site (43), but in fact contains a consensus binding site for the repressor, Sp2.…”
Section: Discussionmentioning
confidence: 99%
“…Several variations of DHFR have been found in noncoding regions, which may relate to the variability of DHFR activity found in the current study. A 19 bp deletion polymorphism within intron 1 (43) has been found to enhance gene expression (44,45). This increased expression was thought to be due to loss of another Sp1 transcription factor binding site (43), but in fact contains a consensus binding site for the repressor, Sp2.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals homozygous for the deletion (À/À) have lower mean plasma total homocysteine than those homozygous for the insertion ( þ / þ ), 40 with the (À/À) individuals also having been shown to have 4.8-fold greater DHFR mRNA expression in lymphocytes compared with ( þ / þ ) carriers. 42 The 5 0 -upstream 9-bp repeat polymorphism (homozygous 6R carriers) 43 and 3 0 -UTR SNP (rs34764978) (C/T and T/T carriers) 44 have also been associated with enhanced mRNA expression.…”
Section: Tymsmentioning
confidence: 99%
“…natural diet rich in folate and vitamin supplements. In the latter case, folic acid is the supplemented active substance, which needs the aforementioned DHFR enzyme to achieve a naturally occurring reduced form [16]. Polymorphism of the DHFR-19-bp gene by generating its overexpression disrupts folate metabolic processes, and thus also disturbs the level of SAM, DNA methylation processes and finally, modifies the transcription factor binding sites.…”
Section: Vitamin Chemoprevention?mentioning
confidence: 99%
“…The cohort study the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial demonstrated an approx. 20% increase in the risk of breast cancer in postmenopausal women supplemented with a daily dose of folic acid above 400 μg [16]. Figueiredo et al [5] reported that the amount of folic acid exceeding 400 μg saturates the DHFR enzyme.…”
Section: Vitamin Chemoprevention?mentioning
confidence: 99%